Recent developments in composite solid electrolytes for all-solid-state lithium batteries and their applications in deep-sea environment - Hui Chang; Xin Zhang; Weiya Li; Haojing Liu; Hongkai Hu; Zhihong Liu; Wei Liu; Yongcheng Jin (Next Materials)
The development of power supply devices with higher performance, superior security, and extended lifespan is imperative for their application in extreme conditions characterized by high pressure and low temperature, such as deep-sea environments. As the important energy storage devices, lithium batteries have been used to supply energy for some types of marine scientific equipment. Compared with traditional lithium-ion batteries (LIBs), all-solid-state batteries present high level of safety, higher energy density, and high-pressure and low temperature tolerance. In recent years, solid-state electrolytes have gained considerable focus as a core ingredient in solid-state lithium batteries. Composite solid electrolytes (CSEs) combine the superior strength and large conductivity of solid inorganic electrolytes (SIEs) and excellent process ability of solid polymer electrolytes (SPEs), marking them one of the most attractive materials for solid electrolytes in the marine environment. However, most CSEs still have challenges with low ionic conductivity and insufficient interface compatibility. The construction of CSEs membranes with outstanding electrochemical performance and electrolyte-electrode interface under low temperature and high pressure is a powerful approach to developing solid-state lithium rechargeable batteries suitable for marine scientific equipments. In this review, we firstly introduce marine environment in terms of depth of seawater and seafloor topography. Then, we list current marine scientific research devices and analyze energy supply status. Thirdly, the different sample preparation techniques have been summarized. The effects of low temperature and high pressure on electrolyte and interfaces between electrolyte and electrode are discussed in detail. Finally, we present the progress of CSEs employed in all-solid-state lithium storage batteries under low-temperature and high-pressure environment. The purpose of this review is to emphasize the inspiration of solid-state lithium rechargeable batteries with CSEs for powering deep-sea scientific research devices.